(untitled) (Journal of Sciences & Technology, 2019)
The advancement made on sequencing technology over the last years has been impressive. However, a number of new instruments were commercialized, the most attractive and promising one was the MinIon from Oxford Nanopore technology, UK. It is a small USB device using the nanopore technology to sequence more than 100kbp of DNA single stranded in a short time without pre-amplification or optical steps. This review focusses on the use of the new sequencing technology to improve the molecular and the precision diagnostic. Herein, we expose the employment of MinIon device for characterization, monitoring and detection of mutations in infectious agents but also its application in precision diagnosis and mutation analysis in clinical oncology and immunologic research.